2007
DOI: 10.1177/0363546507307507
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Comparison of High School and College Wrestling Injuries

Abstract: Rates and patterns of wrestling injury differ between high school and college and between practice and matches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
96
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 28 publications
8
96
1
2
Order By: Relevance
“…[2][3][4][5] This study represents the largest, most comprehensive epidemiologic investigation of high school shoulder injuries to date. Investigations into the rates and patterns of shoulder injuries across both boys'and girls' sports as described in this study increase our understanding of injury risk factors and spur the development of injury prevention programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] This study represents the largest, most comprehensive epidemiologic investigation of high school shoulder injuries to date. Investigations into the rates and patterns of shoulder injuries across both boys'and girls' sports as described in this study increase our understanding of injury risk factors and spur the development of injury prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Sport participation is beneficial to overall health, but carries with it a significant risk of injury. Shoulder injuries are noted to be among the top 3 most common body sites of injury among high school football players, 2,3 the most common site among high school and collegiate wrestlers, 4 and the fifth most common site among all high school athletes. 5 Types of sports-related shoulder injury are varied but can generally be categorized as either acutely traumatic or secondary to overuse.…”
mentioning
confidence: 99%
“…(year 2) school years, injury and exposure data were prospectively collected from athletes via the High School Sport-Related Injury Surveillance System, RIO (Reporting Information Online, Columbus, OH). 3,[24][25][26] An Internet-based injury surveillance system, RIO records injury data in US high school sports. Sports studied during years 1 and 2 were boys' football, soccer, basketball, wrestling, and baseball and girls' soccer, basketball, volleyball, and softball.…”
mentioning
confidence: 99%
“…In the literature review, it was detected that infectious dermatologic diseases are more commonly found in wrestlers since wrestling is a sport branch in which skin to skin contact is the most common (22)(23)(24); related studies focus on wrestlers.…”
Section: Resultsmentioning
confidence: 99%